SECURITIES CROWDFUNDING: KAJIAN REGULASI PASAR MODAL DI INDONESIA - Mutiara, Yusian; Wishnu Kurniawan, S.H., M.H.; Nikmah Mentari, S.H., M.H. (JIL : Journal of Indonesian Law, 2024)
The concept of crowdfunding based on securities offerings allows micro, small and medium enterprises to obtain funds and capital through securities crowdfunding. However, investors in this case have a great risk of loss because issuers who issue securities through securities crowdfunding are not companies like issuers in the Stock Exchange. This causes many of them to be very new, so they may not have good management. This research aims to see how the law can protect securities crowdfunding investors. This research uses a juridical-normative approach to see the legal protection of securities crowdfunding investors in Law No. 4 of 2023 concerning Strengthening and Development of the Financial Sector and the Financial Services Authority Regulation (POJK). The results of this study indicate that Law No. 4 of 2023 concerning Development and Strengthening of the Financial Sector and Financial Services Authority Regulation (POJK) No. 16/POJK.04/2021 have provided legal protection to securities crowdfunding investors, namely preventive protection and repressive protection. However, regarding the protection of the parties, it is still hampered by several factors, such as investor ignorance, unpreparedness of human resources, and slow handling of complaints by the organizers. In addition, the prospectus issued by the issuer often cannot be confirmed for accuracy, due to differences in information disclosure standards such as securities offerings on the Stock Exchange and the absence of involvement of professional institutions.